DAILY OCCURRENCE OF WHALE SHARKS (Rhincodon typus) AND MIGRATION OF NEW INDIVIDUALS IN THE WATERS OF KWATISORE - Maruanaya, Yan; Mirino, Manuel; Sumaryono (Bogor Agricultural University, 2025)
The waters of Kwatisore are recognized as a consistent aggregation site for whale sharks (Rhincodon typus) throughout the year, with an increasing number of individuals observed. Understanding individual occurrence patterns is essential for monitoring population dynamics and conservation planning. This study aimed to analyze the daily occurrence of whale sharks based on individual identification and assess the entry of new individuals into the Kwatisore waters. Data collection was conducted from November 2023 to January 2024. A total of 27 male individuals were recorded, with a cumulative 592 sightings. Body lengths ranged from 2.5 to 5 meters, dominated by individuals approximately 3.5 meters in length. Spatial distribution of daily occurrences followed the positioning of anchored lift-net fishing gear (bagan), while temporal distribution showed a higher occurrence during morning hours. In 2023, 13 new individuals were recorded entering the area. The daily appearances were dominated by juvenile-sized individuals, and sighting frequency varied among individuals. Spatial and temporal patterns were strongly influenced by anchovy (Stolephorus spp.) catches from the bagan gear, while the entry of new individuals contributed to the growing aggregation of whale sharks in the Kwatisore waters. Keywords: whale sharks, daily occurrence, new individual migration